Understanding personal risk of oropharyngeal cancer: risk-groups for oncogenic oral HPV infection and oropharyngeal cancer - D’Souza, G (Ann Oncol, 2017)
BACKGROUND: Incidence of human papillomavirus (HPV)-related oropharyngeal cancer is increasing. There is interest in identifying healthy individuals most at risk for development of oropharyngeal cancer to inform screening strategies. PATIENTS AND METHODS: All data are from 2009 to 2014, including 13 089 people ages 20–69 in the National Health and Nutrition Examination Survey (NHANES), oropharyngeal cancer cases from the Surveillance, Epidemiology, and End Results (SEER 18) registries (representing ∼28% of the US population), and oropharyngeal cancer mortality from National Center for Health Statistics (NCHS). Primary study outcomes are (i) prevalence of oncogenic HPV DNA in an oral rinse and gargle sample, and (ii) incident oropharyngeal squamous cell cancer. RESULTS: Oncogenic oral HPV DNA is detected in 3.5% of all adults age 20–69 years; however, the lifetime risk of oropharyngeal cancer is low (37 per 10 000). Among men 50–59 years old, 8.1% have an oncogenic oral HPV infection, 2.1% have an oral HPV16 infection, yet only 0.7% will ‘ever’ develop oropharyngeal cancer in their lifetime. Oncogenic oral HPV prevalence was higher in men than women, and increased with number of lifetime oral sexual partners and tobacco use. Men who currently smoked and had ≥5 lifetime oral sexual partners had ‘elevated risk’ (prevalence = 14.9%). Men with only one of these risk factors (i.e. either smoked and had 2–4 partners or did not smoke and had ≥5 partners) had ‘medium risk’ (7.3%). Regardless of what other risk factors participants had, oncogenic oral HPV prevalence was ‘low’ among those with only ≤1 lifetime oral sexual partner (women = 0.7% and men = 1.7%). CONCLUSIONS: Screening based upon oncogenic oral HPV detection would be challenging. Most groups have low oncogenic oral HPV prevalence. In addition to the large numbers of individuals who would need to be screened to identify prevalent oncogenic oral HPV, the lifetime risk of developing oropharyngeal caner among those with infection remains low.